Prone positioning as a bridge to recovery from refractory hypoxaemia following lung transplantation. (25th April 2017) - Riera, Jordi; Maldonado, Carolina; Mazo, Cristopher; Martínez, María; Baldirà, Jaume; Lagunes, Leonel; Augustin, Salvador; Roman, Antonio; Due, Maria; Rello, Jordi; Levine, Deborah J.
Abstract: OBJECTIVES: Refractory hypoxaemia is the leading cause of mortality in the postoperative period after lung transplantation. The role of prone positioning as a rescue therapy in this setting has not been assessed. We evaluated its effects in lung transplant recipients presenting refractory hypoxaemia following the surgery. METHODS: Prospectively collected data from 131 consecutive adult patients undergoing lung transplantation between January 2013 and December 2014 were evaluated. Twenty-two patients received prone position therapy. Indications, associated complications, time to initiation and duration of the manoeuvre were analysed and the effects of prone position on gas exchange were evaluated. Finally, outcomes in this cohort were compared against the rest of lung transplant recipients. RESULTS: Prone positioning was more frequently implemented within the first 72 h (68.2%) and its main indication was primary graft dysfunction. The manoeuvre was maintained during a median of 21 h. After prone position, the pressure of arterial oxygen/fraction of inspired oxygen ratio significantly increased from 81.0 mmHg [interquartile range (IQR) 71.5–104.0] to 220.0 (IQR 160.0–288.0) ( P  < 0.001). No complications related with the technique were reported. Patients who underwent the manoeuvre had longer hospital stay [50.0 days (IQR 36.0–67.0) vs 30.0 (IQR 23.0–56.0), P  = 0.006] than the rest of the population. No differences were found comparing either 1-year mortality (9.1% vs 15.6%; P  = 0.740) or 1-year graft function [forced expiratory volume in 1 second of 70.0 (IQR 53.0–83.0) vs 68.0 (IQR 53.5–80.5), P  = 0.469]. CONCLUSIONS: Prone positioning is safe and significantly improves gas exchange in patients with refractory hypoxaemia after lung transplantation. It should be considered as a possible treatment in these patients.